Deciphering ADFGVX messages from the Eastern Front of World War I. Issue 2 (4th March 2017) - Lasry, George; Niebel, Ingo; Kopal, Nils; Wacker, Arno
ABSTRACT: In the last months of World War I (WW I), the German Army and diplomatic services used the ADFGVX hand-cipher system to encrypt radio messages between Germany and its outposts and stations in the Balkans, the Black Sea, and in the Middle East. Hundreds of cryptograms were intercepted from July to December 1918 by British and U.S. military intelligence, who were able to recover most of the keys and decipher most of the cryptograms using manual cryptanalysis methods. Fortunately, the original cryptograms have been preserved by James Rives Childs, the U.S. officer assigned to G.2 A.6, the SIGINT section of American Expeditionary Forces (AEF) in Paris, and they appear in his book, General Solution of the ADFGVX Cipher System, published by Aegean Press Park in 2000. In this article, the authors present the results of an effort toward the complete cryptanalysis of the messages, and an analysis of their contents. The authors present a new computerized method for the ciphertext-only cryptanalysis of ADFGVX messages which they developed for that purpose. They also provide details on how all the keys were recovered and almost all the messages decrypted, despite the low quality of significant parts of the intercepted material. The analysis of the messages in their historical context provides a unique insight into key events, such as the withdrawal of the German troops from Romania, and the impact of the Kiel Mutiny on communications. Both events had major political and military consequences for Germany in the Eastern Front. Cryptanalysis allowed the Entente Powers to closely monitor those events as well as others developments, also highlighting inherent weaknesses in German cryptographic and cryptanalytic capabilities. The authors plan to publish online all the decrypted messages.